Determinación de la prevalencia de giardia spp. En caninos domésticos (canis lupus familiaris) en la clínica veterinaria dino sur del distrito metropolitano de Quito. - Taco Vaca, Ana Cristina (Ecuador: Latacunga: Universidad Técnica de Cotopaxi (UTC)., 2020)
The objective of this research was to determine the prevalence of Giardia spp., In domestic canines (canis lupus familiaris), through coprological examinations in patients who attend the Dino Sur Veterinary Clinic, for this purpose the use of the method of concentration for coproparasitic exams, the method is called flotation enrichment or Faust Method, with 33% zinc sulfate, which verifies the presence of this protozoan in the collected samples. For the investigation there were different characteristics to be evaluated, such as the classification of the canines in groups of age ranges (1 to 3 years, 4 to 6 years, 7 to more years), and the influence of sex.The study was conducted in a population of 100 canines, obtaining 23% of animals positive to Giardia and 77% cases negative to Giardia. Of which, according to the age ranges of 1 to 3 years, 11% of cases of Giardia were established, from 4 to 6 years 6% of cases of Giardia, and finally from 7 to more years 6% were presented of positive cases to Giardia. Similarly, it was analyzed according to the sex variable, 14% of males and 9% of females tested positive. On the contrary 32% of males and 45% of females were negative.The corresponding clinical file was used for each patient, gathering important information such as; name of the patient, age, sex, race, if it correctly carries its schedule of vaccines and deworming, type of food and environment in which the patient is located, as well as of a parasitological results sheet that was socialized to the owners of the Patients evaluated, the social and environmental importance of the correct handling and care of pets that live with humans. La presente investigación tuvo como objetivo determinar la prevalencia de Giardia spp., en caninos domésticos (canis lupus familiaris), a través de exámenes coprológicos en los pacientes que acuden a la Clínica Veterinaria Dino Sur, para ello se ha planteado la utilización del método de concentración para exámenes coproparasitarios, el método se le denomina enriquecimiento por ...